Question Number 166377 by cortano1 last updated on 19/Feb/22
![Given A= ((((1/2) (1/2))),(( a b)) ) . If A^3 = A^2 then 2a−3b=?](https://www.tinkutara.com/question/Q166377.png)
$$\:\:\mathrm{Given}\:\mathrm{A}=\begin{pmatrix}{\frac{\mathrm{1}}{\mathrm{2}}\:\:\:\:\:\:\frac{\mathrm{1}}{\mathrm{2}}}\\{\:\:\mathrm{a}\:\:\:\:\:\:\:\:\mathrm{b}}\end{pmatrix}\:.\:\mathrm{If}\:\mathrm{A}^{\mathrm{3}} =\:\mathrm{A}^{\mathrm{2}} \\ $$$$\:\mathrm{then}\:\mathrm{2a}−\mathrm{3b}=? \\ $$
Answered by bobhans last updated on 19/Feb/22
![A^2 = ((((1/2) (1/2))),(( a b)) ) ((((1/2) (1/2))),(( a b)) ) = ((((1/4)+(1/2)a (1/4)+(1/2)b)),(((1/2)a+ab (1/2)a+b^2 )) ) A^3 = ((((1/4)+(1/2)a (1/4)+(1/2)b)),(((1/2)a+ab (1/2)a+b^2 )) ) ((((1/2) (1/2))),(( a b)) ) = ((((1/8)+(1/2)a+(1/2)ab (1/8)+(1/4)a+(1/4)b+(1/2)b^2 )),(((1/4)a+(1/2)ab+(1/2)a^2 +ab^2 (1/4)a+(1/2)ab+(1/2)a^2 +b^3 )) ) { (((1/4)+(1/2)a=(1/8)+(1/2)a+(1/2)ab⇒ab=(1/4))),(((1/4)+(1/2)a=(1/8)+(1/4)a+(1/4)b+(1/2)b^2 ⇒(1/8)+(1/4)a=(1/4)b+(1/2)b^2 )) :} ⇒ 1+2a=2b+4b^2 ∧ a=(1/(4b)) ⇒1+(1/(2b))=2b+4b^2 ; 8b^3 +4b^2 −2b−1=0 ⇒(2b+1)(4b^2 −1)=0 ⇒(2b+1)^2 (2b−1)=0 → { ((b=−(1/2)⇒a=−(1/2))),((b=(1/2)⇒a=(1/2))) :} ∴ 2a−3b = { ((−1+(3/2)=(1/2))),((1−(3/2)=−(1/2))) :}](https://www.tinkutara.com/question/Q166382.png)
$$\:\:\mathrm{A}^{\mathrm{2}} =\begin{pmatrix}{\frac{\mathrm{1}}{\mathrm{2}}\:\:\:\:\:\frac{\mathrm{1}}{\mathrm{2}}}\\{\:\:\mathrm{a}\:\:\:\:\:\:\:\mathrm{b}}\end{pmatrix}\:\begin{pmatrix}{\frac{\mathrm{1}}{\mathrm{2}}\:\:\:\:\:\frac{\mathrm{1}}{\mathrm{2}}}\\{\:\:\mathrm{a}\:\:\:\:\:\:\mathrm{b}}\end{pmatrix}\:=\:\begin{pmatrix}{\frac{\mathrm{1}}{\mathrm{4}}+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{a}\:\:\:\frac{\mathrm{1}}{\mathrm{4}}+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{b}}\\{\frac{\mathrm{1}}{\mathrm{2}}\mathrm{a}+\mathrm{ab}\:\:\:\:\frac{\mathrm{1}}{\mathrm{2}}\mathrm{a}+\mathrm{b}^{\mathrm{2}} }\end{pmatrix} \\ $$$$\:\mathrm{A}^{\mathrm{3}} =\begin{pmatrix}{\frac{\mathrm{1}}{\mathrm{4}}+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{a}\:\:\:\:\:\frac{\mathrm{1}}{\mathrm{4}}+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{b}}\\{\frac{\mathrm{1}}{\mathrm{2}}\mathrm{a}+\mathrm{ab}\:\:\:\:\:\frac{\mathrm{1}}{\mathrm{2}}\mathrm{a}+\mathrm{b}^{\mathrm{2}} }\end{pmatrix}\:\begin{pmatrix}{\frac{\mathrm{1}}{\mathrm{2}}\:\:\:\:\frac{\mathrm{1}}{\mathrm{2}}}\\{\:\:\mathrm{a}\:\:\:\:\:\mathrm{b}}\end{pmatrix} \\ $$$$\:\:\:\:\:\:=\begin{pmatrix}{\frac{\mathrm{1}}{\mathrm{8}}+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{a}+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{ab}\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\:\frac{\mathrm{1}}{\mathrm{8}}+\frac{\mathrm{1}}{\mathrm{4}}\mathrm{a}+\frac{\mathrm{1}}{\mathrm{4}}\mathrm{b}+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{b}^{\mathrm{2}} }\\{\frac{\mathrm{1}}{\mathrm{4}}\mathrm{a}+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{ab}+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{a}^{\mathrm{2}} +\mathrm{ab}^{\mathrm{2}} \:\:\:\:\frac{\mathrm{1}}{\mathrm{4}}\mathrm{a}+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{ab}+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{a}^{\mathrm{2}} +\mathrm{b}^{\mathrm{3}} }\end{pmatrix} \\ $$$$\:\begin{cases}{\frac{\mathrm{1}}{\mathrm{4}}+\cancel{\frac{\mathrm{1}}{\mathrm{2}}\mathrm{a}}=\frac{\mathrm{1}}{\mathrm{8}}+\cancel{\frac{\mathrm{1}}{\mathrm{2}}\mathrm{a}}+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{ab}\Rightarrow\mathrm{ab}=\frac{\mathrm{1}}{\mathrm{4}}}\\{\frac{\mathrm{1}}{\mathrm{4}}+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{a}=\frac{\mathrm{1}}{\mathrm{8}}+\frac{\mathrm{1}}{\mathrm{4}}\mathrm{a}+\frac{\mathrm{1}}{\mathrm{4}}\mathrm{b}+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{b}^{\mathrm{2}} \Rightarrow\frac{\mathrm{1}}{\mathrm{8}}+\frac{\mathrm{1}}{\mathrm{4}}\mathrm{a}=\frac{\mathrm{1}}{\mathrm{4}}\mathrm{b}+\frac{\mathrm{1}}{\mathrm{2}}\mathrm{b}^{\mathrm{2}} }\end{cases} \\ $$$$\:\Rightarrow\:\mathrm{1}+\mathrm{2a}=\mathrm{2b}+\mathrm{4b}^{\mathrm{2}} \:\wedge\:\mathrm{a}=\frac{\mathrm{1}}{\mathrm{4b}} \\ $$$$\Rightarrow\mathrm{1}+\frac{\mathrm{1}}{\mathrm{2b}}=\mathrm{2b}+\mathrm{4b}^{\mathrm{2}} \:;\:\mathrm{8b}^{\mathrm{3}} +\mathrm{4b}^{\mathrm{2}} −\mathrm{2b}−\mathrm{1}=\mathrm{0} \\ $$$$\Rightarrow\left(\mathrm{2b}+\mathrm{1}\right)\left(\mathrm{4b}^{\mathrm{2}} −\mathrm{1}\right)=\mathrm{0} \\ $$$$\Rightarrow\left(\mathrm{2b}+\mathrm{1}\right)^{\mathrm{2}} \left(\mathrm{2b}−\mathrm{1}\right)=\mathrm{0}\:\rightarrow\begin{cases}{\mathrm{b}=−\frac{\mathrm{1}}{\mathrm{2}}\Rightarrow\mathrm{a}=−\frac{\mathrm{1}}{\mathrm{2}}}\\{\mathrm{b}=\frac{\mathrm{1}}{\mathrm{2}}\Rightarrow\mathrm{a}=\frac{\mathrm{1}}{\mathrm{2}}}\end{cases} \\ $$$$\:\therefore\:\mathrm{2a}−\mathrm{3b}\:=\:\begin{cases}{−\mathrm{1}+\frac{\mathrm{3}}{\mathrm{2}}=\frac{\mathrm{1}}{\mathrm{2}}}\\{\mathrm{1}−\frac{\mathrm{3}}{\mathrm{2}}=−\frac{\mathrm{1}}{\mathrm{2}}}\end{cases} \\ $$